Identification and comparison of missed nursing care in the United States of America and South Korea - Lee, Eunjoo; Kalisch, Beatrice J. (Journal of clinical nursing, 2021)
Aims and objectives This study aimed to identify and compare missed nursing care types and reasons between South Korea and the United States of America. Background Patient safety has become a significant task of the healthcare delivery systems worldwide. The omission of nursing care constitutes a growing concern because it threatens both patient safety and nursing care quality. Design This study used a cross‐sectional, descriptive and comparative design. Methods Data were collected from registered nurses working in two university‐affiliated tertiary hospitals and a general hospital in Korea and a Midwest United States tertiary hospital. In addition, the STROBE checklist was used in this study. Results While substantial, the level of missed nursing care reported by Korean nurses was lower than that of United States nurses. Only three nursing care activities, setting up meals, patient assessment and skin/wound care, did not significantly differed between two countries. More basic nursing care types such as ambulation, feeding and mouth care were missed more than others in both countries. The reasons for missed care differed between two countries. However, both Korean and US nurses reported labour resource problems as reasons for missed care. Conclusions Although the types of missed nursing care differed significantly between countries, both Korean and US nurses reported labour resource problems for the top reasons for missed care. Thus, comparing missed nursing care could assist nursing administrators in developing strategies to improve care quality and patient safety. Relevance to clinical practice The level and reasons for missed nursing care are very influential factors for patient outcomes and patient safety. Appropriate skill mix and staffing are needed to decrease extent of missed care, so that enhancing patient safety and quality of nursing care.